AaPDR3, a PDR Transporter 3, Is Involved in Sesquiterpene β-Caryophyllene Transport in Artemisia annua - Fu, Xueqing; Shi, Pu; He, Qian; Shen, Qian; Tang, Yueli; Pan, Qifang; Ma, Yanan; Yan, Tingxiang; Chen, Minghui; Hao, Xiaolong; Liu, Pin; Li, Ling; et al. (Frontiers in Plant Science, 2017)
Artemisinin, a sesquiterpenoid endoperoxide, isolated from the plant Artemisia annua L., is widely used in the treatment of malaria. Another sesquiterpenoid, β-caryophyllene having antibiotic, antioxidant, anticarcinogenic and local anaesthetic activities, is also presented in A. annua. The role played by sesquiterpene transporters in trichomes and accumulation of these metabolites is poorly understood in A. annua and in trichomes of other plant species. We identified AaPDR3, encoding a pleiotropic drug resistance (PDR) transporter from A. annua that is located to the plasma membrane. Expression of AaPDR3 is tissue-specifically and developmentally regulated in A. annua. GUS activity is primarily restricted to T-shaped trichomes of old leaves and roots of transgenic A. annua plants expressing proAaPDR3: GUS. The level of β-caryophyllene was decreased in transgenic A. annua plants expressing AaPDR3-RNAi while transgenic A. annua plants expressing increased levels of AaPDR3 accumulated higher levels of β-caryophyllene. When AaPDR3 was expressed in transformed yeast, yeasts expressing AaPDR3 accumulated more β-caryophyllene, rather than germacrene D and β-farnesene, compared to the non-expressing control.